Assessing the effectiveness of EU's regional policies: a new approach - Oscar Bajo-Rubio; Carmen Díaz-Roldán; Simón Sosvilla-Rivero (European Regional Science Association (ERSA), 2004)
In this paper, we propose a new methodology for the assessment of EU's regional policies, making use of the HERMIN macro econometric model. A major feature of our approach is that allows us to compare the actual evolution of the economy under analysis, with and without European funds, so that we should be able to assess in a more accurate way the effectiveness of the EU aid over the period of analysis. An empirical application of the methodology is also offered, using as a case study an Objective 1 Spanish region, Castilla - La Mancha, traditionally backward but showing in last years a special dynamism. Key words: EU's regional policies, Community Support Frameworks, HERMIN-Spain model, Castilla-La Mancha JEL classification: H50, H54, R58
Keywords: H50; H54; R58; 330; EU's regional policies; Community Support Frameworks; HERMIN-Spain model; Castilla-La Mancha